Ranmor Mutation Management to Improve the Quality of Public Services to Realize Precision Police at Kudus Police - Wibowo, Imam Eko Akbar Yudha (Advances in Police Science Research Journal, 2024)
Kudus Police Traffic Unit data from 2021 to September 2022 Shows the completion of Ranmor in Kudus Regency. Problem with The process of making Ranmor because the time is unclear, the mechanism is long and is considered complicated by taxpayers and must prepare quite large administrative costs. Method A qualitative approach and the type of research proposed were used in this research. Primary and secondary data sources were taken using data collection techniques interviews, observations, and documents. In addition, data validity is required and interactive model analysis techniques. Use of management theory as an analytical tool which consists of management elements and functions. The research results conclude Ranmor’s treatment management at Kudus Police has not met the service requirements public and the provisions of Regident Ranmor due to inconsistencies in the Source Organizational Power (SDO) and the system and methods of the Kudus Police Traffic Police Registration Unit. From these problems, problem solving steps reflect ideal conditions and efforts to improve public services oriented towards the concept of "Precision Police" so that realizing quality service.